English grammar in use ; A self-study reference and practice book for intermediate leaners of English. With answers. Fifth Edition. - Murphy, Raymond (Cambridge University Press, 2019)
Raymond Murphy's English Grammar in Use is the first choice for intermediate (B1-B2) learners and covers all the grammar you will need at this level. This book with answers has clear explanations and practice exercises that have helped millions of people around the world improve their English. It is perfect for self-study and can also be used by teachers as a supplementary book in classrooms.